CONTAINER TRANSPORTATIONS BETWEEN EUROPE AND ASIA - T. Sakulyeva; A. Perminova (Вестник университета)
The main transit corridors on cargo delivery between the countries of Europe and Asia are considered. «Bottlenecks» of using the Trans-Siberian Railway at the organization of the international rail transit transport are allocated.